2008
DOI: 10.1021/jo701926r
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric Measurement of the CH/π Interaction Involved in the Molecular Recognition of Saccharides by Aromatic Compounds

Abstract: Can a benzene molecule differentiate between two isomeric carbohydrates? It is generally accepted that two factors govern molecular recognition: complementarity and preorganization. Preorganization requires the presence of cavities for positioning the host's groups of complementary nature to those of the guest. This study shows that, in fact, groups should be complementary to recognize each other (for the case presented here, it is controlled by the CH/pi interaction) but preorganization is not essential. Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…A similar interaction energy value for the CH/p interaction has been observed by Bautista-Ibanes et al using calorimetric experiments. [21] They have also shown, using 1 H NMR experiments, that all three hydrogen atoms of the apolar face of the mannopyranose derivate, namely H1, H3, H5, are involved in the interaction. The inclusion of all apolar CH hydrogen atoms in the CH/p interaction in solution have also been suggested by the IR experiments.…”
Section: H T U N G T R E N N U N G (Hn-p) Distance Values Must Be Madmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar interaction energy value for the CH/p interaction has been observed by Bautista-Ibanes et al using calorimetric experiments. [21] They have also shown, using 1 H NMR experiments, that all three hydrogen atoms of the apolar face of the mannopyranose derivate, namely H1, H3, H5, are involved in the interaction. The inclusion of all apolar CH hydrogen atoms in the CH/p interaction in solution have also been suggested by the IR experiments.…”
Section: H T U N G T R E N N U N G (Hn-p) Distance Values Must Be Madmentioning
confidence: 97%
“…[18] This shows that these interactions are not simply hydrophobic but they can exist without solvent effects and physical attractive forces play an important role. These complexes were also studied by IR experiments in gas phase and in solution, [19,20] calorimetric experiments in solution [21] and NMR experiments. [17,[22][23][24][25] These interactions are also often considered examples of CH/p interactions.…”
mentioning
confidence: 99%
“…In these structures, the aromatic group interacts with either the upper or the lower face of the sugar. The most stable group of complexes (8,9,10) involves the interaction of the arene with one O-H and one C-H group of the upper face of the sugar. The next group of complexes (1, 2, 3, 5, and 6) is higher in energy by 1-3 kcal mol −1 , and, except for (3), involve the interaction of only C-H groups of the lower face of the sugar.…”
Section: Model Complexesmentioning
confidence: 99%
“…Amino acids having aromatic side chains (tryptophan, tyrosine and phenylalanine) are frequently found in protein active sites which recognize carbohydrates, and the importance of the associated arene-carbohydrate interactions is well recognized [6][7][8][9]. A number of experimental [10,11] and theoretical [12][13][14][15] studies have shown that there are major contributions to these intermolecular interactions involving the aliphatic C-H and O-H groups which point towards the aromatic system. The corresponding protein crystal structures display mainly C-H-interactions, but in the binary complexes, fucose-toluene and ␣-methyl glucose-toluene, the most stable structures involve O-H-interactions, which are reflected in their infrared spectra [11].…”
Section: Introductionmentioning
confidence: 99%
“…The carbohydrate-aromatic interactions, which are sometimes denoted as CH/p interactions, were used for recognition of carbohydrates by artificial receptors [11][12][13][14]. The carbohydrate-aromatic interactions have been studied extensively both by experimental [15][16][17][18][19][20][21][22][23] and by theoretical [24][25][26][27][28][29][30][31][32][33][34][35] methods. The carbohydrate recognition processes involve desolvation of water molecules from the carbohydrate molecule.…”
Section: Introductionmentioning
confidence: 99%